MODEL PEMBELAJARAN BAHASA BERBASIS ASET KOMUNITAS DI SEKOLAH MUSLIM THAILAND - Nur Cholilah; Garnetta Liya Widyanti (Jurnal AbdiMas Nusa Mandiri, 2026)
This study is motivated by the urgency of developing language learning in Islamic educational institutions that require innovative teaching methods which are effective and efficient, while simultaneously preserving Islamic identity within Muslim communities in Thailand. The study examines the implementation of the Asset-Based Community Development (ABCD) approach in language learning at Bamrung Islam School, Southern Thailand. The ABCD approach utilizes community assets, such as human resources and cultural networks, to develop interactive learning methods aimed at improving students’ competencies in English, Arabic, and Qur’anic studies. Data were collected through qualitative research methods, including observation, needs mapping, and evaluative reflection. The findings indicate that the ABCD approach is able to optimize local potential by enhancing students’ learning motivation, self-confidence, and active participation, while also encouraging innovation in teaching practices. This model has the potential to serve as a reference for community empowerment initiatives in Islamic educational institutions at the international level.